The SunPy Project: An interoperable ecosystem for solar data analysis - , The SunPy Community; Barnes, Will T.; Christe, Steven; Freij, Nabil; Hayes, Laura A.; Stansby, David; Ireland, Jack; Mumford, Stuart J.; Ryan, Daniel F.; Shih, Albert Y. (Frontiers in Astronomy and Space Sciences, 2023)
The SunPy project is a community of scientists and software developers creating an ecosystem of Python packages for solar physics. The project includes the sunpy core package as well as a set of affiliated packages. The sunpy core package provides general purpose tools to access data from different providers, read image and time series data, and transform between commonly used coordinate systems. Affiliated packages perform more specialized tasks that do not fall within the more broad scope of the sunpy core package. In this article, we give a high-level overview of the SunPy project, how it is separate from the core sunpy package, and how the project curates and fosters the affiliated package system. We demonstrate how components of the sunpy ecosystem, including the sunpy and several affiliated packages, work together to enable multi-instrument data analysis workflows. We also describe members of the SunPy project and how the project fosters interacts with the wider solar physics and scientific Python communities. Finally, we discuss the future direction and priorities of the SunPy project.